Field reports form for submitting seasonal observations of Iowa birds, Michael C. Newlon, winter 1982-1983. - Newlon, Michael C.et al (1982)
Winter report of birds found in eastern Iowa contributed by Michael C. Newlon. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed